PENGARUH KUALITAS PRODUK, PROMOSI DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN ROKOK MARLBORO (Studi Kasus Pada Perempuan Perokok di Kecamatan Tembalang Semarang) - Apriliandini Fitriana Dewi; Wahyu Hidayat; Sari Listyorini (Jurnal Ilmu Administrasi Bisnis, 2015)
This research is conducted to discover the influence of product quality, Promotion, and Brand Image on Purchase decision to Women Smoker in Tembalang District. Type of this research is Explanatory Resesarch. Population used for this research is consumer that bought Marlboro. Samples used for this research are 100 respondents whom counted with Slovin formula.  Sample collection sample is Non Probability Sampling. Questioner and Interview used to collecting data for this research. To analyze the data method used is linear regression analysis.Result of this research show that product quality, promotion, and brand image has impact on purchase decision. Product quality, promotion, and brand image are able to explain (punctuate) purchase decision variable in amount of 87.8% which influenced by product quality (32.7%), Promotion (15.6%), Brand Image (87.7%). These variables have significant impact on purchase decision of Marlboro in Tembalang District with the most influential variable is Brand Image.Author suggests that the producer give more education to its salesperson regarding the product, make some innovation in the design of the packaging and the cigarette filter in order to attract the consumer, especially women smoker.